Factors associated with malnutrition in demented and non-demented elderly residing in the community of Korea: a cross-sectional descriptive and analytical study - Jinhee Kwon; Jung Hee Kim; Hyeonjin Jeong; Jung Suk Lee (Korean Journal of Community Nutrition)
Objectives This study aimed to investigate and compare factors associated with malnutrition according to the presence or absence of dementia in community-dwelling elderly people. Methods Needs assessment data from 311 long-term care insurance (LTCI) recipients (dementia group 203; non-dementia group 108) that participated in the second pilot program of the integrated care model in community care settings under the Korean LTCI system were used. Descriptive statistical analysis, independent t-test, or Fisher's exact test were conducted on the sociodemographic characteristics, health and functional status, and nutritional status of the dementia and non-dementia groups. Logistic regression analysis was conducted to identify factors associated with malnutrition in the dementia and non-dementia groups. Results Malnutrition occurred in 33.5% and 26.9% of participants in the dementia and non-dementia groups, respectively. In the dementia group, living with family rather than living alone (odds ratio [OR]: 3.81; 95% confidence interval [CI]: 1.50–9.66; P = 0.031), increase in Korean Activities of Daily Living (K-ADL) score (OR: 1.35; 95% CI: 1.17–1.55; P < 0.001), and increase in the Neuropsychiatric Inventory-Questionnaire score (OR: 1.02; 95% CI: 1.01–1.03; P = 0.005) were associated with a higher risk of malnutrition. In the non-dementia group, the risk of malnutrition increased as the K-ADL score increased (OR: 1.20; 95% CI: 1.04–1.39; P = 0.011) and in the depressed group (OR: 2.84; 95% CI: 1.04–7.74; P = 0.042). Conclusions The study results confirmed the necessity of nutritional management for community-dwelling LTCI recipients. When developing a nutritional management program, considering the differences in factors related to malnutrition between the dementia and non-dementia groups is important. This study proposes policies for improving the LTCI system in terms of nutritional management and the utilization of community resources.